Peningkatan efikasi diri dalam pengambilan keputusan karir melalui pelatihan perencanan karir (FENOMENA, 2021)
Self-efficacy describes a person's confidence in his skills and ability to manage execution and regulate performance in certain areas. Several research results show that self-efficacy is positively related to career decision making. This study aims to analyse changes in self-efficacy in career decision making after career planning training. The subjects of this study were 26 high school students of class XII who were following tutoring. This research is experimental research by conducting pre-test and post-test training. The analysis was conducted by comparing the mean or average value of self-efficacy in making career decisions before and after career planning training. The training module was also assessed by three professional judgments related to the material, presentation, language, and training design. Based on the assessments of three professional judgments, the research module was good in terms of material (75%), presentation (91.7%), language (83.3%), and training design (83.3%). The mean value on the pre-test (33.35) is lower than the mean value on the post-test (39.91). Therefore, it can be concluded that career planning training can improve self-efficacy in making career decisions.